Climate Change and Livelihoods in Selected Rural Coastal Communities in Waterside Local Government Area in Ogun State - Adeniyi, Adekunle A.; Aderogba, Kofo (NIU Journal of Social Sciences; Vol 5 No 3 (2019): KIU Journal of Social Sciences, Vol. 5 No. 3, September 2019, 2019)
This study was on climate change and rural livelihoods in Makun-Omi, Ode-Omi and Iwopin communities in Waterside Local Government Area in Ogun State, Nigeria. Ex post facto design was adopted and three hundred and forty nine respondents randomly selected participated in the study. Analysis of data generated from an adapted Climate Change and Livelihoods’ Questionnaire showed that participants’ livelihoods activities were crop production, fishing and fishing related activities and non-farm activities. Eight types of manifestation of climate change ranked were flooding mean score 3.7, temperature mean score 3.64, rainfall mean score 3.6, water salinity mean score 3.54. Sea level mean score 1.51, heat waves mean score 1.48, drought with mean score 1.45 and storm activity mean score 1.36. The correlation matrix showed that temperature (r = -0.4221), rainfall (r = -0.0788), flooding (r = -0.7469) and water salinity (r = -0.1949) have negative relationship with livelihoods. It also showed that temperature (r= -0.6480), rainfall (r = -0.5754), flooding (r = -0.5813) and water salinity (r = -0.0547) all had negative relationship with livelihoods income at 0.05 alpha level. Therefore, the two null hypotheses were rejected. It is concluded that climate change increased poor livelihoods through reduction in agricultural production, poor outcomes of fishing and fishing related activities, low non-farm activities outcomes, loss of livelihoods income. It is recommended that inhabitants of these communities should be trained on new strategies for sustainable livelihoods strategies. Keywords: climate change, rural, livelihoods, coastal, communities.